Stress Tolerance-Related Genetic Traits of Fish Pathogen Flavobacterium psychrophilum in a Mature Biofilm - Levipan, Héctor A.; Quezada, Johan; Avendaño-Herrera, Ruben (Frontiers in Microbiology, 2018)
Flavobacterium psychrophilum is the causative agent of bacterial cold-water disease and rainbow trout fry syndrome, and hence this bacterium is placed among the most important salmonid pathogens in the freshwater aquaculture industry. Since bacteria in biofilms differ substantially from free-living counterparts, this study sought to find the main differences in gene expression between sessile and planktonic states of F. psychrophilum LM-02-Fp and NCMB1947T, with focus on stress-related changes in gene expression occurring during biofilm formation. To this end, biofilm and planktonic samples were analyzed by RNA sequencing to detect differentially expressed candidate genes (DECGs) between the two growth states, and decreasing the effects of interstrain variation by considering only genes with log2-fold changes ≤ -2 and ≥ 2 at Padj-values ≤ 0.001 as DECGs. Overall, 349 genes accounting for ~15% of total number of genes expressed in transcriptomes of F. psychrophilum LM-02-Fp and NCMB1947T (n = 2327) were DECGs between biofilm and planktonic states. Approximately 83% and 81% of all up- and down-regulated candidate genes in mature biofilms, respectively, were assigned to at least one gene ontology term; these were primarily associated with the molecular function term ‘catalytic activity’. We detected a potential stress response in mature biofilms, characterized by a generalized down-regulation of DECGs with roles in the protein synthesis machinery (n = 63, primarily ribosomal proteins) and energy conservation (seven ATP synthase subunit genes), as well as an up-regulation of DECGs involved in DNA repair (ruvC, recO, phrB1, smf, and dnaQ) and oxidative stress response (cytochrome C peroxidase, probable peroxiredoxin, and a probable thioredoxin). These results support the idea of a strategic trade-off between growth-related processes and cell homeostasis to preserve biofilm structure and metabolic functioning. In addition, LDH-based cytotoxicity assays and an intraperitoneal challenge model for rainbow trout fry agreed with the transcriptomic evidence that the ability of F. psychrophilum to form biofilms could contribute to the virulence. Finally, the reported changes in gene expression, as induced by the plankton-to-biofilm transition, represent the first transcriptomic guideline to obtain insights into the F. psychrophilum biofilm lifestyle that could help understand the prevalence of this bacterium in aquaculture settings.